PENGARUH PERILAKU ADAPTIF TERHADAP KETERAMPILAN SOSIAL SISWA DI SMP NEGERI 1 MANDREHE UTARA - Damanik, Hosianna Rodearni; Telaumbanua, Arisman (Jurnal Suluh Pendidikan, 2024)
This study aims to evaluate the influence of adaptive behavior on the social skills of seventh-grade students at SMP Negeri 1 Mandrehe Utara. In the educational context, adaptive behavior refers to students' ability to adjust to the school environment, both in interactions with peers and teachers. This adaptive behavior develops through social interactions and the ability to adapt to new situations. The research uses an associative method with a quantitative approach and collects data through questionnaires completed by the students. The results show a significant positive influence between adaptive behavior and students' social skills. Students who exhibit good adaptive behavior tend to have higher social skills. This study underscores the importance of developing adaptive behavior in enhancing students' social skills in the school environment. With good adaptive behavior, students can interact, collaborate, and understand others' perspectives more easily, thus creating a harmonious and productive learning environment. Therefore, greater attention is necessary to developing students' adaptive behavior to improve and enhance their social skills in the educational setting.